Assessment of vocational guidance: the berufsbilder test - Leal Melo-silva, Lucy; Pasian, Sonia Regina; Alzira Bonfim, Talma; De Fátima Assoni, Renata (The Spanish Journal of Psychology, 2008)
The object of this study is to assess informative possibilities of some technical indicators of the Test of Photos of Professions (BBT – Berufsbilder test), a projective method to clarify professional inclination, proposed by Martin Achtnich. This psychological evaluation technique is composed of 96 photos of professionals, performing various types of activities. The test subject classifies the photos into three groups: positive (agreeable), negative (disagreeable) and indifferent (neutral). Among those chosen positively, five preferences are chosen and a story is developed that includes them, an activity that is requested two times during the Vocational Guidance process: in the beginning (or middle) and at the end of the intervention. In this study, 160 stories were created by 80 youths, between 15 and 20 years of age, in public and private schools in a mid-sized Brazilian city. The stories were compared in three analytical categories: protagonist, professional conflict and resolution. The results were submitted to Wilcoxon nonparametric statistical analysis (p < .05), significant and relevant indicators of resolution being found in the process of occupational choice. This technical resource was shown, from this empirical evidence, to be promising for use in evaluation of intervention processes of Vocational Guidance.